2018
DOI: 10.1016/j.stemcr.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Endogenous α-Synuclein Accumulation in Oligodendrocyte Precursor Cells Potentially Induces Inclusions in Multiple System Atrophy

Abstract: SummaryGlial cytoplasmic inclusions (GCIs), commonly observed as α-synuclein (α-syn)-positive aggregates within oligodendrocytes, are the pathological hallmark of multiple system atrophy. The origin of α-syn in GCIs is uncertain; there is little evidence of endogenous α-syn expression in oligodendrocyte lineage cells, oligodendrocyte precursor cells (OPCs), and mature oligodendrocytes (OLGs). Here, based on in vitro analysis using primary rat cell cultures, we elucidated that preformed fibrils (PFFs) generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 19 publications
(23 reference statements)
2
75
1
Order By: Relevance
“…Drosophila serves as a powerful model organism for investigating human neurodegeneration in large part due to the high conservation of disease‐related genes (McGurk, Berson, & Bonini, ; Rubin et al, ). To explore the relevance of our differentially expressed genes, we identified their rat, mouse, and human orthologs and cross‐referenced this list with additional publicly available lists of differentially expressed genes identified in transcriptomic studies of MSA animal models (Kaji et al, ; Schafferer et al, ) or human post‐mortem MSA brains (Langerveld, Mihalko, DeLong, Walburn, & Ide, ; Mills, Ward, Kim, Halliday, & Janitz, ). We also compared the ortholog list to genes that have been identified as candidate risk genes for any human α‐synucleinopathy by examining genome‐wide association or whole exome sequencing studies from MSA (X. Gu et al, ; Sailer et al, ), PD (Chang et al, ; Guo et al, ; Jansen et al, ; Li et al, ; Quadri et al, ; Robak et al, ; Sandor et al, ; Schormair et al, ; Shulskaya et al, ; Siitonen et al, ; Ylönen et al, ), or DLB (Guerreiro et al, ; Keogh et al, ; Peuralinna et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila serves as a powerful model organism for investigating human neurodegeneration in large part due to the high conservation of disease‐related genes (McGurk, Berson, & Bonini, ; Rubin et al, ). To explore the relevance of our differentially expressed genes, we identified their rat, mouse, and human orthologs and cross‐referenced this list with additional publicly available lists of differentially expressed genes identified in transcriptomic studies of MSA animal models (Kaji et al, ; Schafferer et al, ) or human post‐mortem MSA brains (Langerveld, Mihalko, DeLong, Walburn, & Ide, ; Mills, Ward, Kim, Halliday, & Janitz, ). We also compared the ortholog list to genes that have been identified as candidate risk genes for any human α‐synucleinopathy by examining genome‐wide association or whole exome sequencing studies from MSA (X. Gu et al, ; Sailer et al, ), PD (Chang et al, ; Guo et al, ; Jansen et al, ; Li et al, ; Quadri et al, ; Robak et al, ; Sandor et al, ; Schormair et al, ; Shulskaya et al, ; Siitonen et al, ; Ylönen et al, ), or DLB (Guerreiro et al, ; Keogh et al, ; Peuralinna et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…While NG2 cells were initially thought to only give rise to oligodendrocytes [3,16,32,45,48], it is now known they can also differentiate into astrocytes [10,47,48]. Recently, two groups reported co-localization of α-synuclein neuropathology with NG2 cells in MSA patient samples [15,24]. Using immunofluorescence with an NG2-specific antibody to determine co-localization with αsynuclein, we found that neither Tg mouse model developed α-synuclein inclusions in NG2 cells (Online Resource, Fig.…”
Section: Tg(snca*a53t +/+ ) Mice Inoculated With Msa Develop Neuronalmentioning
confidence: 89%
“…20 Kaji et al reported that GCI-like accumulations are more likely to appear in progenitor cells than mature oligodendrocytes, using cultured cells as a model. 21 Uemura et al reported accumulation of α-synuclein in oligodendrocytes of aged mice inoculated with recombinant α-synuclein fibrils. 22 However, in most cases of MSA, GCIs are the main pathology, and neuronal inclusions are rarely observed.…”
Section: Remaining Issues Concerning α-Synuclein Propagationmentioning
confidence: 99%